Investigating common clinical presentations in first opinion small animal consultations using direct observation. (2nd May 2015) - Robinson, N. J.; Dean, R. S.; Cobb, M.; Brennan, M. L.
Abstract : Understanding more about the clinical presentations encountered in veterinary practice is vital in directing research towards areas relevant to practitioners. The aim of this study was to describe all problems discussed during a convenience sample of consultations using a direct observation method. A data collection tool was used to gather data by direct observation during small animal consultations at eight sentinel practices. Data were recorded for all presenting and non‐presenting specific health problems discussed. A total of 1901 patients were presented with 3206 specific health problems discussed. Clinical presentation varied widely between species and between presenting and non‐presenting problems. Skin lump, vomiting and inappetence were the most common clinical signs reported by the owner while overweight/obese, dental tartar and skin lump were the most common clinical examination findings. Skin was the most frequently affected body system overall followed by non‐specific problems then the gastrointestinal system. Consultations are complex, with a diverse range of different clinical presentations seen. Considering the presenting problem only may give an inaccurate view of the veterinary caseload, as some common problems are rarely the reason for presentation. Understanding the common diagnoses made is the next step and will help to further focus questions for future research.